2021
DOI: 10.3390/ijms222112068
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide in Plants: Crosstalk with Other Signal Molecules in Response to Abiotic Stresses

Abstract: Hydrogen sulfide (H2S) has recently been considered as a crucial gaseous transmitter occupying extensive roles in physiological and biochemical processes throughout the life of plant species. Furthermore, plenty of achievements have been announced regarding H2S working in combination with other signal molecules to mitigate environmental damage, such as nitric oxide (NO), abscisic acid (ABA), calcium ion (Ca2+), hydrogen peroxide (H2O2), salicylic acid (SA), ethylene (ETH), jasmonic acid (JA), proline (Pro), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 106 publications
0
19
0
Order By: Relevance
“…Recent studies have shown that, in plant systems, the application of exogenous H 2 S donors can significantly enhance the tolerance of plants to abiotic stresses, such as drought, high salinity, and toxic heavy metals [ 45 , 60 , 61 ]. More and more attention has been paid to the mechanism by which the signaling molecule H 2 S in the plant system regulates other signaling pathways involved in various abiotic stress responses [ 62 ]. It had been reported that H 2 S could improve drought tolerance in rice by re-establishing redox homeostasis and activating the ABA signaling pathway [ 63 ], and could also alleviate aluminum toxicity by reducing aluminum content in rice [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that, in plant systems, the application of exogenous H 2 S donors can significantly enhance the tolerance of plants to abiotic stresses, such as drought, high salinity, and toxic heavy metals [ 45 , 60 , 61 ]. More and more attention has been paid to the mechanism by which the signaling molecule H 2 S in the plant system regulates other signaling pathways involved in various abiotic stress responses [ 62 ]. It had been reported that H 2 S could improve drought tolerance in rice by re-establishing redox homeostasis and activating the ABA signaling pathway [ 63 ], and could also alleviate aluminum toxicity by reducing aluminum content in rice [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the pathway of NO modulating the crosstalk between ABA and H 2 O 2 and activating the calcium signaling pathway has also been further revealed [ 31 ]. Wang et al mentioned that extracellular Ca 2+ and ABA promote stomatal closure by promoting H 2 O 2 to produce calcium signals dependent on NO synthesis [ 32 ]. In Arabidopsis ABI mutants, H 2 O 2 and NO activate calcium signals depending on cyclic guanosine 3′,5′-monophosphate (cGMP), which likely acts upstream of calcium signals.…”
Section: Molecular Mechanisms Of Crosstalk Between Ca 2+ ...mentioning
confidence: 99%
“…During H 2 S-mediated stress mitigation, H 2 S interacts with other signalling components, e.g. H 2 S-NO, H 2 S-ABA, H 2 S-SA, H 2 S-Ca 2+ and H 2 S-MT (Wang et al 2021a) under abiotic stress. This integrated cross-talk in temperature stress mitigation is discussed below (Fig.…”
Section: Crosstalk Of H 2 S With Other Components During Temperature ...mentioning
confidence: 99%
“…H 2 S‐NO, H 2 S‐ABA, H 2 S‐SA, H 2 S‐Ca 2+ and H 2 S‐MT (Wang et al . 2021a) under abiotic stress. This integrated cross‐talk in temperature stress mitigation is discussed below (Fig.…”
Section: Crosstalk Of H2s With Other Components During Temperature St...mentioning
confidence: 99%